Late intervention for type II endoleak is not determined by early sac diameter or volume changes after EVAR - Sneyers Bernard; Verbraeken Viktor; Laenen Annouschka; Coudyzer Walter; Mufty Hozan; Houthoofd Sabrina; Fourneau Inge; Maleux Geert (Radiology and Oncology)
To compare the diagnostic accuracy and predictive value of aneurysm sac volume measurement versus maximum diameter measurement of abdominal aortic aneurysm sac after endovascular aneurysm repair (EVAR) in patients with type II endoleak.